Scientific mapping of behavioral addictions in the case of peruvian journals - Salas-Blas, Edwin (2021)
Background: Publications on addictive behaviors have been increasing including their contextual heterogeneity in different virtual platforms in order to generate visibility. Objective: it was to identify the networks of collaboration, authorship and keywords on addictive behaviors. Method: Scientific mapping and bibliometric indicators were used to analyze the evolution of addictive behaviors in indexed and non-indexed journals in Peru. Results: 38% of articles were single authorship, 43 of them use quantitative data (81%), 23 worked with young participants (53.5%), 37 are empirical studies (69.9%) and internet addiction was more frequent (39.6 %). Peruvian journals in SCI since 2006 have presented at least an index value h = 1. Conclusion: there is evidence of difficulty in tracking studies on addictive behaviors in Peruvian journals, added to the lack of clear regulations, generate a complex task that influences its lack of visibility